2020
DOI: 10.1093/mnras/staa917
|View full text |Cite
|
Sign up to set email alerts
|

A closer look at the spur, blob, wiggle, and gaps in GD-1

Abstract: The GD-1 stream is one of the longest and coldest stellar streams discovered to date, and one of the best objects for constraining the dark matter properties of the Milky Way. Using data from Gaia DR2 we study the proper motions, distance, morphology and density of the stream to uncover small scale perturbations. The proper motion cleaned data shows a clear distance gradient across the stream, ranging from 7 to 12 kpc. However, unlike earlier studies that found a continuous gradient, we uncover a distance mini… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 83 publications
(113 reference statements)
6
36
0
Order By: Relevance
“…Gaps of scales of approximately 10 • were found in this stream using SDSS and these were associated with the encounter with sub-halos by Carlberg (2016). This was confirmed by Banik et al (2021) analyzing the stellar density perturbations from accurate measurements of the morphology (de Boer et al 2020) of this streams using Gaia data combined with photometry from Pan-STARRS (Chambers et al 2016). They found that the data indicates that these perturbations should come from sub-halos, and that their abundance and masses are compatible with the expected from CDM from simulations.…”
Section: Stellar Streamsmentioning
confidence: 64%
“…Gaps of scales of approximately 10 • were found in this stream using SDSS and these were associated with the encounter with sub-halos by Carlberg (2016). This was confirmed by Banik et al (2021) analyzing the stellar density perturbations from accurate measurements of the morphology (de Boer et al 2020) of this streams using Gaia data combined with photometry from Pan-STARRS (Chambers et al 2016). They found that the data indicates that these perturbations should come from sub-halos, and that their abundance and masses are compatible with the expected from CDM from simulations.…”
Section: Stellar Streamsmentioning
confidence: 64%
“…The morphology of the gap and the spur observed in the GD-1 stream can be reproduced by numerical models of the stream interacting with a massive object in the Milky Way halo (Bonaca et al 2019;de Boer et al 2020), and the interaction might have elevated the stream's velocity dispersion. However, similarly high values of velocity dispersion were measured in the Palomar 5 tidal tails (σ = 2.1 ± 0.4 km s −1 , Kuzma et al 2015) and the ATLAS-Aliqa Uma complex (σ = 4.8 ± 0.4 km s −1 , Li et al 2020).…”
Section: Summary and Discussionmentioning
confidence: 91%
“…To date, there is about a dozen of known cold streams in the inner regions of the Galaxy (Malhan et al 2018;Ibata et al 2019). Among those, the best studied correspond to the stream associated with the globular cluster Palomar 5 (Odenkirchen et al 2003), and GD-1 (Grillmair & Dionatos 2006), whose progenitor remains undetected to date, likely because it was completely disrupted (Malhan & Ibata 2019;de Boer et al 2020). Bearing in mind the limitations discussed in §4.1, it interesting to estimate the number of ultra-wide binaries that can potentially form in those systems.…”
Section: Ultra-wide Binaries In Cold Tidal Streamsmentioning
confidence: 99%